2017
DOI: 10.1101/220608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread Genotype-Phenotype Correlations in Intellectual Disability

Abstract: BackgroundLinking genotype to phenotype is a major aim of genetics research, yet many complex conditions continue to hide their underlying biochemical mechanisms. Recent research provides evidence that relevant gene-phenotype associations are discoverable in the study of intellectual disability (ID). Here we expand on that work, identifying distinctive gene interaction modules with unique enrichment patterns reflective of associated clinical features in ID.MethodsTwo hundred twelve forms of monogenic ID were c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Regarding the two prioritized genes ( PRPF8 and RBM14 ) as possible novel candidates to ASD, PRPF8 is highly expressed in brain and encodes a protein that acts as a scaffold for spliceosome complexes, being the most evolutionarily conserved protein of the spliceosome [Grainger & Beggs, ; Maciejewski & Padgett, ]. PRPF8 is essential to pre‐mRNA splicing and is required in all tissues, being recently described as a main molecular hub linking autism and epilepsy in gene‐interaction networks [Casanova, Gerstner, Sharp, & Casanova, ]. Furthermore, we identified another six ASD individuals harboring de novo variants in PRPF8 , resulting in a nominal significant number compared to the expected rate to this gene [Samocha et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the two prioritized genes ( PRPF8 and RBM14 ) as possible novel candidates to ASD, PRPF8 is highly expressed in brain and encodes a protein that acts as a scaffold for spliceosome complexes, being the most evolutionarily conserved protein of the spliceosome [Grainger & Beggs, ; Maciejewski & Padgett, ]. PRPF8 is essential to pre‐mRNA splicing and is required in all tissues, being recently described as a main molecular hub linking autism and epilepsy in gene‐interaction networks [Casanova, Gerstner, Sharp, & Casanova, ]. Furthermore, we identified another six ASD individuals harboring de novo variants in PRPF8 , resulting in a nominal significant number compared to the expected rate to this gene [Samocha et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to address clinically associated confounds, we also compared ASD risk genes to a group of syndromic ID‐associated genes (not linked with autism), which we had compiled and reported in a previous study [Casanova et al, , ]. We found that gene/protein lengths were significantly longer in the ASD genes compared to the ID genes ( P < 0.0001).…”
Section: Resultsmentioning
confidence: 97%
“…This agrees with our earlier study [Casanova et al, ], which reported a functional enrichment of epigenetic regulators among many of the same genes. These genes are also strongly implicated in autism‐associated genetic syndromes accompanied by widespread dysmorphic features, indicating that they play vital roles not just in corticogenesis but morphogenesis in general [Casanova et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations